In vivo imaging models of bone and brain metastases and pleural carcinomatosis with a novel human EML4‐ALK lung cancer cell line. Issue 3 (17th February 2015) - Nanjo, Shigeki; Nakagawa, Takayuki; Takeuchi, Shinji; Kita, Kenji; Fukuda, Koji; Nakada, Mitsutoshi; Uehara, Hisanori; Nishihara, Hiroshi; Hara, Eiji; Uramoto, Hidetaka; Tanaka, Fumihiro; Yano, Seiji
Abstract : EML4‐ALK lung cancer accounts for approximately 3–7% of non‐small‐cell lung cancer cases. To investigate the molecular mechanism underlying tumor progression and targeted drug sensitivity/resistance in EML4‐ALK lung cancer, clinically relevant animal models are indispensable. In this study, we found that the lung adenocarcinoma cell line A925L expresses an EML4‐ALK gene fusion (variant 5a, E2:A20) and is sensitive to the ALK inhibitors crizotinib and alectinib. We further established highly tumorigenic A925LPE3 cells, which also have the EML4‐ALK gene fusion (variant 5a) and are sensitive to ALK inhibitors. By using A925LPE3 cells with luciferase gene transfection, we established in vivo imaging models for pleural carcinomatosis, bone metastasis, and brain metastasis, all of which are significant clinical concerns of advanced EML4‐ALK lung cancer. Interestingly, crizotinib caused tumors to shrink in the pleural carcinomatosis model, but not in bone and brain metastasis models, whereas alectinib showed remarkable efficacy in all three models, indicative of the clinical efficacy of these ALK inhibitors. Our in vivo imaging models of multiple organ sites may provide useful resources to analyze further the pathogenesis of EML4‐ALK lung cancer and its response and resistance to ALK inhibitors in various organ microenvironments. Abstract : In the present study, we identified a novel EML4‐ALK positive lung cancer cell line (variant 5 ; E2:A20) and further stablished in vivo imaging models for pleural carcinomatosis, bone metastasis, and brain metastasis, all of which are significant clinical concerns of advanced EML4‐ALK lung cancer. Our in vivo imaging models of multiple organ sites may provide useful resources to analyze further the pathogenesis of EML4‐ALK lung cancer and its response and resistance to ALK inhibitors in various organ microenvironments.